2015
DOI: 10.1091/mbc.e14-12-1648
|View full text |Cite
|
Sign up to set email alerts
|

Wnt ligand–dependent activation of the negative feedback regulator Nkd1

Abstract: Nkd1, a negative feedback regulator of the Wnt pathway, localizes with Dvl2 to the putative Wnt signalosome, where it becomes activated by Wnt. Activated Nkd1 moves away from the membrane to become more cytosolic, where it interacts with β-catenin to prevent nuclear accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…NKD1 is an antagonist of the canonical Wnt/β-catenin pathway (8). Dysregulation of Wnt signaling is at the root of multiple diseases, including cancer (17). Guo et al (12) demonstrated that specific NKD1 mutations may promote Wnt-dependent tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…NKD1 is an antagonist of the canonical Wnt/β-catenin pathway (8). Dysregulation of Wnt signaling is at the root of multiple diseases, including cancer (17). Guo et al (12) demonstrated that specific NKD1 mutations may promote Wnt-dependent tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that NKD1 antagonizes Wnt signaling by preventing the nuclear accumulation of β-catenin 7 8 . However, activation of the Wnt/β-catenin signaling pathway results in the up-regulation of downstream genes such as NKD1 9 .…”
mentioning
confidence: 99%
“…Mutations in RNF43 could be subdued after ETC-1922159 has suppressed the Wnt pathway as has been shown in [25]. NKD1 is enigmatic in nature and known to be a negative regulator of the Wnt pathway [102]. Mutations in NKD1 have been found to be prevalent in colorectal cancer cases [103].…”
Section: Resultsmentioning
confidence: 84%